Oxidation catalyst as well as preparation method and application thereof

By using an oxidation catalyst composed of rare earth metal oxides and alkaline earth metal oxides in wet oxidation technology, the catalyst has a pore structure of 1-2nm and 10-50nm, solving the problems of catalyst instability and low COD removal efficiency in the prior art, and achieving efficient removal of small molecular organic matter and reuse of carbon.

CN119701921AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311280367.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

When the existing wet oxidation technology treats organic wastewater, the reaction conditions are harsh, the catalyst is unstable, the active components are easily lost, the COD removal efficiency is low, and when small molecular organic matter such as acetic acid is present, the hydrothermal stability of the catalyst is affected, resulting in equipment corrosion.

Method used

An oxidation catalyst is provided, which comprises a rare earth metal oxide and an alkaline earth metal oxide and has a pore structure of 1-2 nm and 10-50 nm. The catalyst is obtained by a preparation method including preparing a precursor containing a support, a rare earth metal and an alkali metal, and is treated with acetic acid, washed, dried, and molded.

Benefits of technology

The catalyst has mild conditions for use, high selectivity and good stability of small molecule organic matter (acetic acid), can efficiently remove organic pollutants under mild conditions, reduce carbon emissions, and achieve carbon reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701921A_ABST
    Figure CN119701921A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalysts, in particular to an oxidation catalyst and a preparation method and application thereof. The oxidation catalyst is characterized in that the catalyst comprises a carrier and active components, and the active components comprise a rare earth metal oxide and an alkaline earth metal oxide; the catalyst comprises a pore channel with the pore diameter of 1-2 nm and a pore channel with the pore diameter of 10-50 nm. The active components of the oxidation catalyst comprise the rare earth metal oxide and the alkaline earth metal oxide, and the catalyst comprises the pore channel with the pore diameter of 1-2 nm and the pore channel with the pore diameter of 10-50 nm, so that the catalyst is mild in use condition, high in selectivity of small molecular organic matter (acetic acid) and good in stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalysts, and in particular to an oxidation catalyst and a preparation method and application thereof. Background Art

[0002] Wet oxidation is a technology developed in the 1950s to treat organic wastewater. This method is a chemical process that uses air or pure oxygen as an oxidant to oxidize organic pollutants into inorganic substances such as CO2 and water or small molecular organic substances in the liquid phase under high temperature (125-320℃) and high pressure (0.5-20MPa) conditions. This process is energy-saving and environmentally friendly and can treat toxic, harmful, and high-concentration organic wastewater.

[0003] In the carbon conversion process of oxidizing organic pollutants into CO2 or small molecular organic matter, the former increases the emission of CO2 in the atmospheric environment, while the latter does not effectively solve the problem of organic pollutants in water. Therefore, it is hoped that new technologies can achieve carbon reuse, solve carbon emission problems, and reduce the greenhouse effect.

[0004] In the wet oxidation reaction process, although the wet oxidation efficiency can be improved and the reaction conditions can be reduced by adding a catalyst, high temperature and high pressure process conditions are still required to obtain a higher COD removal rate. At the same time, the carrier and active components are easily lost under harsh reaction conditions. Therefore, the COD removal efficiency of the catalyst gradually decreases during long-term operation. When the COD removal efficiency is relatively low, the main organic matter in the wastewater is small molecule compounds, among which small molecule acids such as acetic acid are more common. When acetic acid is present, the hydrothermal stability of the catalyst is affected, and as the temperature rises, the corrosion of steel equipment and instruments increases exponentially. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of harsh reaction conditions, unstable catalyst, easy loss of active components and low COD removal efficiency in the prior art when treating organic wastewater with wet oxidation technology, and to provide an oxidation catalyst and a preparation method and application thereof. The oxidation catalyst has the advantages of mild use conditions, high selectivity for small molecule organic matter (acetic acid) and good stability.

[0006] In order to achieve the above objectives, the first aspect of the present invention provides an oxidation catalyst, which comprises a carrier and an active component, wherein the active component comprises a rare earth metal oxide and an alkaline earth metal oxide; the catalyst comprises pores with a pore size of 1-2 nm and pores with a pore size of 10-50 nm.

[0007] The second aspect of the present invention provides a method for preparing an oxidation catalyst, which comprises: (1) preparing a precursor containing a carrier, a rare earth metal and an alkali metal; and (2) treating the precursor with acetic acid, washing, drying and forming.

[0008] The third aspect of the present invention provides a catalyst prepared by the preparation method described in the second aspect of the present invention.

[0009] The fourth aspect of the present invention provides a use of the catalyst described in the first aspect and the catalyst described in the third aspect in catalytic wet oxidation.

[0010] The fifth aspect of the present invention provides a method for treating organic wastewater, which comprises: in the presence of a catalyst, a salt-forming auxiliary agent, organic wastewater and an oxidant are contacted and reacted, and optionally, part of the material after the contact reaction is recycled back to the organic wastewater, and the remaining part is post-treated; the catalyst is the catalyst described in the first aspect and the catalyst described in the third aspect.

[0011] Through the above technical solution, the present invention has the following beneficial effects:

[0012] The active components of the oxidation catalyst of the present invention include rare earth metal oxides and alkaline earth metal oxides, and the catalyst includes pores with a pore size of 1-2nm and pores with a pore size of 10-50nm, so that the catalyst has mild use conditions, high selectivity for small molecule organic matter (acetic acid) and good stability.

[0013] The catalyst of the present invention is applied to catalytic wet oxidation technology, with the goal of generating economically beneficial small-molecule organic matter (acetic acid), carbon is highly selectively converted into small-molecule organic matter (acetic acid), and reacts with the absorbed salt-forming auxiliary agent to generate salt, thereby realizing carbon recycling and reducing carbon emissions; in the preferred embodiment, the salt-forming auxiliary agent contains ammonia, which can realize the recovery and utilization of ammonia. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a flow chart of organic wastewater treatment preferably implemented in the present invention;

[0015] Figure 2 This is the pore volume-pore size distribution diagram of the catalyst prepared in Example 1 of the present invention.

[0016] Description of Reference Numerals

[0017] 1. Absorption tower; 6. Gas phase logistics;

[0018] 2. Oxidation reactor; 7. Absorption liquid;

[0019] 3. Distillation tower; 8. Partial absorption liquid;

[0020] 4. Gas streams containing organic matter soluble in water; 9. Distillation condensate;

[0021] 5. Salt-forming aid; 10. Organic acid salt. DETAILED DESCRIPTION

[0022] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0023] The invention provides an oxidation catalyst, which comprises a carrier and an active component, wherein the active component comprises a rare earth metal oxide and an alkaline earth metal oxide; the catalyst comprises pores with a pore diameter of 1-2 nm and pores with a pore diameter of 10-50 nm.

[0024] The active components of the oxidation catalyst of the present invention include rare earth metal oxides and alkaline earth metal oxides, and the catalyst includes pores with a pore size of 1-2nm and pores with a pore size of 10-50nm, so that the catalyst has mild use conditions, high selectivity for small molecule organic matter (acetic acid) and good stability.

[0025] According to a preferred embodiment of the present invention, based on pore volume, the content of pores with a pore size of 10-50 nm in the catalyst is 30-60%, and the content of pores with a pore size of 1-2 nm is 15-40%. For example, the content of pores with a pore size of 10-50 nm in the catalyst is 40%, 45%, 50%, 55%, 60%; the content of pores with a pore size of 1-2 nm is 15%, 20%, 25%, 30%, 35%, 40%.

[0026] According to a preferred embodiment of the present invention, the carrier comprises a nano-metal oxide coated on the outer surface of the catalyst. By adopting the above preferred solution, the stability of the catalyst can be further improved.

[0027] In the present invention, there is no special requirement for the particle size of the nano metal oxide. According to a preferred embodiment of the present invention, the particle size of the nano metal oxide is 2-10 nanometers.

[0028] In the present invention, the type of the nano metal oxide can be a conventional choice in the art. According to a preferred embodiment of the present invention, the nano metal oxide is a nano Group IVB metal oxide, preferably selected from nano titanium oxide and / or nano zirconium oxide, more preferably nano titanium oxide. By adopting the above preferred embodiment, the stability of the catalyst can be further improved.

[0029] In the present invention, there is no particular restriction on the content of each component in the catalyst. According to a preferred embodiment of the present invention, based on 100 parts by weight, the catalyst comprises: (1) 0.01-10 parts of alkaline earth metal oxide; (2) 0.1-2 parts of rare earth metal oxide; (3) 88-99.89 parts of carrier. By adopting the above preferred embodiment, the selectivity of the catalyst for small molecule organic matter (acetic acid) and the stability of the catalyst can be further improved.

[0030] In the present invention, the carrier can be a conventional choice in the art. According to a preferred embodiment of the present invention, the carrier is at least one of titanium oxide, zirconium oxide and silicon oxide.

[0031] According to a preferred embodiment of the present invention, the carrier is a mixture of titanium oxide, zirconium oxide and silicon oxide, and the weight ratio of titanium oxide, zirconium oxide and silicon oxide in the mixture is preferably 50-70: 8-45: 10-25. By adopting the above preferred embodiment, the selectivity of the catalyst for small molecule organic matter (acetic acid) and the stability of the catalyst can be further improved.

[0032] In the present invention, the type of the alkaline earth metal can be a conventional choice in the art. According to a preferred embodiment of the present invention, the alkaline earth metal is selected from at least one of magnesium, calcium, strontium and barium, preferably at least one of magnesium, calcium and barium, and more preferably barium. By adopting the above preferred embodiment, the selectivity of the catalyst for small molecule organic matter (acetic acid) and the stability of the catalyst can be further improved.

[0033] In the present invention, the type of the rare earth metal can be a conventional choice in the art. According to a preferred embodiment of the present invention, the rare earth metal is selected from at least one of cerium, lanthanum and neodymium. By adopting the above preferred embodiment, the selectivity of the catalyst for small molecule organic matter (acetic acid) and the stability of the catalyst can be further improved.

[0034] The present invention provides a method for preparing an oxidation catalyst, the preparation method comprising:

[0035] (1) preparing a precursor containing a carrier, a rare earth metal and an alkali metal;

[0036] (2) The precursor is treated with acetic acid, washed, dried, and formed.

[0037] The active components of the oxidation catalyst prepared by the method of the present invention include rare earth metal oxides and alkaline earth metal oxides, and the catalyst includes pores with a pore size of 1-2nm and pores with a pore size of 10-50nm, so that the catalyst has mild use conditions, high selectivity for small molecule organic matter (acetic acid) and good stability.

[0038] According to a preferred embodiment of the present invention, step (1) comprises: dissolving a carrier source, a rare earth metal source and an alkaline earth metal source to obtain a mixed solution, adding an alkaline solution to the mixed solution to obtain a slurry, and subjecting the slurry to a first drying and a first calcination to obtain a precursor.

[0039] In the present invention, no special requirements are made on the conditions of the first calcination. In the embodiment of the present invention, calcination at 550° C. for 2 hours is taken as an example to illustrate the advantages of the present invention.

[0040] According to a preferred embodiment of the present invention, in step (1), an alkaline solution is added to obtain a slurry with a pH of 8-10.

[0041] The carrier source in the present invention has a wide selection range, and the carrier source may be, for example, silica sol, titanate TiOSO4, Zr(NO3)4, etc.

[0042] In the present invention, the rare earth metal source is selected from soluble salts of cerium, lanthanum and neodymium, and the alkaline earth metal source is selected from soluble salts of magnesium, calcium, strontium and barium. The alkaline earth metal source is more preferably a soluble salt of barium.

[0043] According to a preferred embodiment of the present invention, the alkaline solution is selected from at least one of aqueous ammonia, urea solution, sodium hydroxide solution, sodium carbonate solution and sodium bicarbonate solution.

[0044] According to a preferred embodiment of the present invention, the first drying method is spray drying.

[0045] According to a preferred embodiment of the present invention, the acetic acid treatment is carried out by hydrothermal treatment in an autoclave.

[0046] According to a preferred embodiment of the present invention, the conditions for acetic acid treatment in step (2) include: the acetic acid concentration is 0.1-2 wt %.

[0047] According to a preferred embodiment of the present invention, the conditions for the acetic acid treatment in step (2) include: a temperature of 80-200°C, preferably 100-150°C.

[0048] According to a preferred embodiment of the present invention, the conditions for acetic acid treatment in step (2) include: a time of 5-120 min, preferably 15-60 min.

[0049] By adopting the aforementioned acetic acid treatment conditions, the small molecule organic matter (acetic acid) selectivity and catalyst stability of the prepared catalyst can be further improved.

[0050] According to a preferred embodiment of the present invention, the molding step in step (2) includes: bonding the dried solid, nano metal oxide and binder, extruding, secondary drying and secondary calcination.

[0051] According to a preferred embodiment of the present invention, the mass ratio of the dried solid to the nano-metal oxide is 80-95:5-20, and the amount of the binder accounts for 2-30% of the total amount of the dried solid, the nano-metal oxide and the binder.

[0052] According to a preferred embodiment of the present invention, the particle size of the nano metal oxide is 2-10 nanometers.

[0053] According to a preferred embodiment of the present invention, the nano metal oxide is a Group IVB metal oxide, preferably selected from nano titanium oxide and / or zirconium oxide, more preferably nano titanium oxide.

[0054] According to a preferred embodiment of the present invention, the binder is selected from at least one of water, liquid paraffin, hydroxymethyl cellulose, polyvinyl alcohol, starch and dextrin and at least one of nitric acid, sulfuric acid, oxalic acid and citric acid.

[0055] In the present invention, there is no particular requirement for the second drying conditions, and the drying at 120° C. is used as an example for illustration.

[0056] In the present invention, there is no special requirement for the conditions of the second calcination, and the calcination at 550° C. is taken as an example for explanation in the embodiment.

[0057] The present invention provides a catalyst prepared by the preparation method of the present invention.

[0058] The present invention provides an application of the catalyst of the present invention in catalytic wet oxidation.

[0059] The catalyst of the present invention is applied to catalytic wet oxidation technology, with the goal of generating economically beneficial small-molecule organic matter (acetic acid), carbon is highly selectively converted into small-molecule organic matter (acetic acid), and reacts with the absorbed salt-forming auxiliary agent to generate salt, thereby realizing carbon recycling and reducing carbon emissions.

[0060] The present invention provides a method for treating organic wastewater, which comprises: in the presence of a catalyst, a salt-forming auxiliary agent, organic wastewater and an oxidant are contacted and reacted, and optionally, a part of the material after the contact reaction is recycled back into the organic wastewater, and the remaining part is post-treated; the catalyst is the catalyst described in the present invention.

[0061] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the pH value of the material after the contact reaction is 2-6.5, preferably 4-6.5.

[0062] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the acetic acid concentration of the material after the contact reaction is 3-20wt%, preferably 3-12wt%.

[0063] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the COD value of the organic wastewater is 40000-250000 mg / L, preferably 40000-150000 mg / L.

[0064] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the salt-forming substance contains at least one of ammonia, sodium hydroxide and potassium hydroxide, preferably contains ammonia, and more preferably, the molar ratio of ammonia to organic wastewater is 1.6-2.5, preferably 1.8-2.2, based on N / C. By adopting the above preferred embodiment, the salt-forming auxiliary agent contains ammonia, and the recovery and utilization of ammonia can be achieved. In the embodiment of the present invention, ammonia is taken as an example to illustrate the advantages of the present invention.

[0065] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the oxidant is an oxygen-containing gas, such as air, pure oxygen or 35-50v% oxygen-enriched gas.

[0066] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the volume ratio of oxygen to organic wastewater in the contact reaction system is 10-400.

[0067] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the reaction temperature is 250-300°C.

[0068] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the reaction pressure is 7-12.0 MPa.

[0069] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the reaction time is 10-150 minutes, preferably 10-120 minutes.

[0070] According to a preferred embodiment of the present invention, the post-treatment method includes distillation crystallization and / or cooling crystallization.

[0071] like Figure 1 As shown, the present invention provides an organic wastewater treatment device, which includes an absorption tower 1, an oxidation reactor 2 and a distillation tower 3 connected in series in sequence, wherein the absorption tower is provided with a feed inlet 4 of a gas stream containing water-soluble organic matter, a feed inlet 5 of a salt-forming auxiliary agent, a discharge port 6 of a gas phase stream, an outlet 7 of an absorption liquid, a feed inlet 9 of a distilled condensate and a feed inlet of a circulating absorption liquid; the oxidation reactor 2 is provided with a feed inlet 7 of an absorption liquid, a discharge port 8 of a part of the absorption liquid and a discharge port of the circulating absorption liquid; the distillation tower is provided with a feed inlet of a part of the absorption liquid, a discharge port 9 of a distilled condensate and a discharge port 10 of an organic acid salt.

[0072] The following will be through examples (in Figure 1The present invention is described in detail in the following examples. In the following examples, the ammonia-containing gas is the reaction gas obtained after the laboratory propylene ammoxidation reaction, and the oxidant used in the wet oxidation reaction process is pure oxygen. The raw materials not specifically described are all commercially available products.

[0073] The schematic flow diagram is a cyclic process, and the key point is that the organic matter is converted into acetic acid in the wet oxidation reactor 2. Therefore, the embodiment only describes the catalyst and the evaluation results.

[0074] Example 1

[0075] 1. Catalyst Preparation

[0076] (1) Slurry spraying: An aqueous solution containing 500 g silica sol (40%), 230 g Ba(NO3)2, 1800 g Zr(NO3)4, 41 g La(NO3)3 and an aqueous solution containing 2350 g TiOSO4 are stirred to obtain a mixed solution A. Under the condition of vigorous stirring in a water bath at 20-80°C, an ammonia solution is slowly added dropwise to the solution A, and the final pH of the solution is controlled to be 9.0 to obtain a slurry B. The slurry B is spray dried to obtain a powder C;

[0077] (2) Support pretreatment: Powder C was calcined at 550°C for 2 h (to obtain a precursor), then treated with 0.5% acetic acid aqueous solution at 150°C in an autoclave for 30 min, cooled, washed with water, and dried at 120°C to obtain powder D;

[0078] (3) Forming: First, 180g of nano-TiO2 powder with a particle size of 2-10 nanometers was dispersed in a mixture of 130g of hydroxymethyl cellulose, 200g of nitric acid and 500g of water, and then bonded with powder D in a bonding machine, extruded, dried at 120°C, and calcined at 550°C to obtain the wet oxidation catalyst. The automatic specific surface and porosity analyzer BET measured the following: Figure 2 From the pore volume-pore size distribution diagram shown, it can be seen that the catalyst includes pores with a pore size of 1-2 nm and pores with a pore size of 10-50 nm, wherein the content of pores with a pore size of 10-50 nm is 48%, and the content of pores with a pore size of 1-2 nm is 22%.

[0079] 2. Catalyst evaluation

[0080] Reaction conditions: temperature 280°C, pressure 7.5 MPa, residence time 45 min, oxygen / liquid volume ratio 300.

[0081] The post-reaction material is sent to distillation and crystallization to obtain acetate.

[0082] The results are shown in Table 1.

[0083] Example 2

[0084] The same as Example 1, except that in step (2), powder C is calcined at 550°C for 2h (to obtain a precursor), treated with 2% acetic acid aqueous solution in an autoclave at 120°C for 30min, cooled, washed with water and dried at 120°C to obtain powder D.

[0085] The pore volume-pore size distribution of the obtained catalyst is Figure 2 Similarly, the content of pores with a pore diameter of 10-50 nm is 53%, and the content of pores with a pore diameter of 1-2 nm is 25%.

[0086] The evaluation method is the same as in Example 1, and the results are shown in Table 1.

[0087] Example 3

[0088] Same as Example 1, except that in step (1), 41 g La(NO3)3 is replaced by 40 g Ce(NO3)3.

[0089] The pore volume-pore size distribution of the obtained catalyst is Figure 2 Similarly, the content of pores with a pore diameter of 10-50 nm is 48%, and the content of pores with a pore diameter of 1-2 nm is 25%.

[0090] The evaluation method is the same as in Example 1, and the results are shown in Table 1.

[0091] Example 4

[0092] Same as Example 1, except that 41 g La(NO3)3 in step (1) is replaced by 35 g La(NO3)3.

[0093] The pore volume-pore size distribution of the obtained catalyst is Figure 2 Similarly, the content of pores with a pore diameter of 10-50 nm is 51%, and the content of pores with a pore diameter of 1-2 nm is 20%.

[0094] The evaluation method is the same as in Example 1, and the results are shown in Table 1.

[0095] Example 5

[0096] Same as Example 1, except that, in step (1), the slurry spraying includes an aqueous solution containing 250 g silica sol (40%), 230 g Ba(NO3)2, 1950 g Zr(NO3)4, 41 g La(NO3)3 and 2150 g TiOSO 4的 The aqueous solution was stirred to obtain a mixed solution A, and the ammonia solution was slowly added dropwise to the solution A in a 20-80°C water bath under vigorous stirring to control the final pH of the solution to 9.0 to obtain slurry B. The slurry B was spray-dried to obtain powder C.

[0097] The pore volume-pore size distribution of the obtained catalyst is Figure 2 Similarly, the content of pores with a pore diameter of 10-50 nm is 41%, and the content of pores with a pore diameter of 1-2 nm is 26%.

[0098] The evaluation method is the same as in Example 1, and the results are shown in Table 1.

[0099] Example 6

[0100] The same as Example 1, except that, in step (1) slurry spraying: an aqueous solution containing 230 g of Ba(NO3)2 and 41 g of La(NO3)3 and an aqueous solution containing 4080 g of TiOSO4 are stirred and mixed to obtain a mixed solution A, and an ammonia solution is slowly added dropwise to the solution A in a 20-80°C water bath under vigorous stirring, and the final pH of the solution is controlled to be 9.0 to obtain slurry B. The slurry B is spray-dried to obtain powder C.

[0101] The pore volume-pore size distribution of the obtained catalyst is Figure 2 Similarly, the content of pores with a pore diameter of 10-50 nm is 39%, and the content of pores with a pore diameter of 1-2 nm is 33%.

[0102] The evaluation method is the same as in Example 1, and the results are shown in Table 1.

[0103] Example 7

[0104] Same as Example 1, except that in step (1), 230 g of Ba(NO3)2 is replaced by 440 g of Mg(NO3)2.

[0105] The pore volume-pore size distribution of the obtained catalyst is Figure 2 Similarly, the content of pores with a pore diameter of 10-50 nm is 45%, and the content of pores with a pore diameter of 1-2 nm is 21%.

[0106] The evaluation method is the same as in Example 1, and the results are shown in Table 1.

[0107] Example 8

[0108] The same as Example 1, except that, in step (3) molding, 260 g of nano ZrO2 powder is first dispersed in a mixture of 130 g of hydroxymethyl cellulose, 200 g of nitric acid and 500 g of water, and then bonded with powder D in a bonding machine, extruded, dried at 120°C and calcined at 550°C to obtain the wet oxidation catalyst.

[0109] The pore volume-pore size distribution of the obtained catalyst is Figure 2 Similarly, the content of pores with a pore diameter of 10-50 nm is 44%, and the content of pores with a pore diameter of 1-2 nm is 26%.

[0110] The evaluation method is the same as in Example 1, and the results are shown in Table 1.

[0111] Example 9

[0112] The same as Example 1, except that, in step (3) molding: a mixture of 130 g of hydroxymethyl cellulose, 200 g of nitric acid and 500 g of water is bonded with powder D in a bonding machine, and the wet oxidation catalyst is obtained by extrusion, drying at 120° C. and calcining at 550° C.

[0113] The pore volume-pore size distribution of the obtained catalyst is Figure 2 Similarly, the content of pores with a pore diameter of 10-50 nm is 51%, and the content of pores with a pore diameter of 1-2 nm is 28%.

[0114] The evaluation method is the same as in Example 1, and the results are shown in Table 1.

[0115] Comparative Example 1

[0116] Same as Example 1, except that, in step (2), carrier pretreatment: powder C was calcined at 550° C. for 2 h to obtain powder D.

[0117] The content of pores with a pore size of 10-50 nm is less than 5% as measured by a fully automatic specific surface and porosity analyzer BET.

[0118] The evaluation method is the same as in Example 1, and the results are shown in Table 1.

[0119] Comparative Example 2

[0120] The same as Example 1, except that in step (2) the carrier is pretreated: powder C is calcined at 550°C for 2h (to obtain a precursor), treated with 0.5% nitric acid aqueous solution at 150°C in an autoclave for 30 minutes, cooled, washed with water and dried at 120°C to obtain powder D.

[0121] The content of pores with a pore size of 10-50 nm is less than 5% as measured by a fully automatic specific surface and porosity analyzer BET.

[0122] The evaluation method is the same as in Example 1, and the results are shown in Table 1.

[0123] Table 1

[0124]

[0125] *1g acetate is equivalent to 1.0667g COD

[0126] *Selectivity calculation: Acetate contribution to COD / (Acetate contribution to COD+Converted COD)*100%

[0127] Example 1 Calculation example: 37441 / (37441+(55000-39300))*100%=69.9%

[0128] * Raw water description: The aqueous solution obtained by absorbing the propylene ammoxidation reaction gas with pure water. The COD varies with the absorption time.

[0129] *Effective conversion rate calculation: (acetic acid ion contribution COD + converted COD) / raw water COD * 100%

[0130] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An oxidation catalyst, characterized in that The catalyst comprises a carrier and an active component, wherein the active component comprises a rare earth metal oxide and an alkaline earth metal oxide; The catalyst comprises pores with a pore diameter of 1-2 nm and pores with a pore diameter of 10-50 nm.

2. The oxidation catalyst according to claim 1, wherein The content of pores with a pore diameter of 10-50 nm in the catalyst is 30-60%, and the content of pores with a pore diameter of 1-2 nm is 15-40%; and / or The carrier comprises a nano metal oxide coated on the outer surface of the catalyst. Preferably, the particle size of the nano metal oxide is 2-10 nanometers. More preferably, the nano metal oxide is a nano Group IVB metal oxide, and more preferably is selected from nano titanium oxide and / or nano zirconium oxide.

3. The oxidation catalyst according to claim 1 or 2, wherein Based on 100 parts by weight, the catalyst comprises: (1) 0.01-10 parts of alkaline earth metal oxide; (2) 0.1-2 parts of rare earth metal oxides; (3) 88-99.89 parts of carrier.

4. The oxidation catalyst according to any one of claims 1 to 3, wherein The carrier is at least one of titanium oxide, zirconium oxide and silicon oxide, more preferably a mixture of titanium oxide, zirconium oxide and silicon oxide, more preferably a weight ratio of titanium oxide, zirconium oxide and silicon oxide in the mixture is 50-70:8-45:10-25; and / or The alkaline earth metal is selected from at least one of magnesium, calcium, strontium and barium, preferably at least one of magnesium, calcium and barium, more preferably barium; and / or The rare earth metal is selected from at least one of cerium, lanthanum and neodymium.

5. A method for preparing an oxidation catalyst, characterized in that: The preparation method comprises: (1) preparing a precursor containing a carrier, a rare earth metal and an alkali metal; (2) The precursor is treated with acetic acid, washed, dried, and formed.

6. The preparation method according to claim 5, wherein: Step (1) comprises: dissolving a carrier source, a rare earth metal source and an alkaline earth metal source to obtain a mixed solution, adding an alkaline solution to the mixed solution to obtain a slurry, and subjecting the slurry to a first drying and a first calcination to obtain a precursor; preferably, the pH of the slurry obtained by adding the alkaline solution is 8-10; and / or The conditions for the acetic acid treatment in step (2) include: Acetic acid concentration is 0.1-2wt%; and / or The temperature is 80-200°C, preferably 100-150°C; and / or The time is 5-120min, preferably 15-60min; and / or The forming step in step (2) includes: bonding the dried solid, nano metal oxide and binder, extruding, secondary drying and secondary calcination; preferably, The mass ratio of the dried solid to the nano-metal oxide is 80-95:5-20, and the amount of the binder accounts for 2-30% of the total amount of the dried solid, the nano-metal oxide and the binder; and / or The particle size of the nano metal oxide is 2-10 nanometers; and / or The nano metal oxide is a Group IVB metal oxide; and / or The binder is selected from at least one of water, liquid paraffin, hydroxymethyl cellulose, polyvinyl alcohol, starch and dextrin and at least one of nitric acid, sulfuric acid, oxalic acid and citric acid.

7. The catalyst prepared by the preparation method according to claim 5 or 6.

8. Use of the catalyst according to any one of claims 1 to 4 and the catalyst according to claim 7 in catalytic wet oxidation.

9. A method for treating organic wastewater, characterized in that: The method comprises: in the presence of a catalyst, a salt-forming auxiliary agent, organic wastewater and an oxidant are contacted and reacted, and optionally, a part of the material after the contact reaction is recycled back into the organic wastewater, and the remaining part is post-processed; The catalyst is the catalyst according to any one of claims 1 to 4 and the catalyst according to claim 7.

10. The method according to claim 9, wherein: The conditions of the contact reaction include: The pH value of the material after the contact reaction is 2-6.5, preferably 4-6.5; and / or The acetic acid concentration of the material after the contact reaction is 3-20wt%, preferably 3-12wt%; and / or The COD value of the organic wastewater is 40000-250000 mg / L, preferably 40000-150000 mg / L; and / or The salt-forming substance comprises at least one of ammonia, sodium hydroxide and potassium hydroxide, preferably ammonia, and more preferably, the molar ratio of ammonia to organic wastewater is 1.6-2.5, preferably 1.8-2.2, calculated on a N / C basis; and / or The oxidant is an oxygen-containing gas; and / or The volume ratio of oxygen to organic wastewater in the contact reaction system is 10-400; and / or The reaction temperature is 250-300°C; and / or The reaction pressure is 7-12.0 MPa; and / or The reaction time is 10-150 minutes, preferably 10-120 minutes; and / or The post-treatment method includes distillation crystallization and / or cooling crystallization.

Citation Information

Patent Citations

  • Metallic oxide mixture catalyzer for purifying organic waste gas and method of preparing the same

    CN101138728A

  • Catalyst for preparing sulfur by selective oxidation of hydrogen sulfide and preparation method thereof

    CN102950000A

  • Wet oxidation catalyst as well as preparation method and application thereof

    CN114471551A

  • Catalyst for olefin oxide reaction

    GB711601A